STRATEGI PENGEMBANGAN KOPERASI INDONESIA MENUJU KOPERASI MANDIRI - Idrus, Salim Al (IQTISHODUNA, 2007)
Cooperation is a social enterprise which its existence should be developed in order to create economic democartion. Cooperation has to act as a counterpart to otherside which power is concentrated on certain groups. More over, as a base of national economic, cooperation not only becomes an institution which members are small scale indutries, buat also becomes an absolute economic power in determining national economicâ€™s power and behavior it self. In realizing it, cooperation must have an ability to become an atunomous institution outisde the government. Having a clear â€œcore businessâ€, cooperation will get the benefit by exploiting business power in its scope. If it is reached, cooperation will become one of the independent economic actors. This independence will make the cooperation developes better than ever. On the other side, cooperation must still have bottom-commitment to the society who has it.